Impacto da ressecção pulmonar por câncer de pulmão nos marcadores inflamatórios após um mês de cirurgia - Araujo, Amanda Souza (2014)
Background: Lung cancer is defined as a malignant injury to respiratory epithelium which is a result of imunological weakness. It is the most prevalent type of cancer with high morbidity and mortality rates. Surgical treament remains the best therapeutic option related to better survival rates in regularly staged patients. Inflamatory markers usage has been assessed in progressive disesases characterized by abnormal lung inflamatory response. This assessment approach is used to indentify early signs of infection, to stratificate risk and to provide adequate therapy choice. Objectives: To assess lung resection impact on blood levels of inflamatory markers, lung function, health related quality of life, anxiety and depression after the first postoperative month. Methods: A prospective cohort study was performed with lung cancer patients undergoing lung resection. Preoperative assessment included sérum fibrinogen levels measurement, C reactive protein (CRP) levels measurement, Six-minute walking test, Karnofsky Performance Status Scale (KPS), spirometry, maximal inspiratory and expiratory pressures, health related quality of life questionnaires such as the Short Form 36 Health Survey Questionnaire, Beck Anxiety (BAI) and Depression (BDI) Inventories. Information on the transoperatory and postoperatory was collected in search of postoperative pulmonary complications. After hospital discharge, patients were followed up by the researcher until the last day of the first postoperative month and same preoperative evaluation was performed with them. Data was statistically treated using the Statistical Package for the Social Sciences – SPSS 21.0. Results: 48 lung cancer patients attended the study with mean age of 60 ± 11,6 years, 29 female (60,4%). 25 patients were staged as Ia and Ib (52,1%). Thoracotomy was the most used surgery technique (31 patients; 64,6%). 12 patients (25%) had postoperative pulmonary complications. After one postoperative month systemic inflamatory markers levels decreased although only CRP levels had significant change (p=0,03). Delta-CRP correlated with Karnofsky (r=0,50; p=0,001), sf36 mental component summary (r=0,34; p=0,01) and fibrinogen levels (r=0,41; p=0,003). There was a tendency of positive correlation of delta-CRP with 6MWT (r=0,28; p=0,05). Patients undergone video-assisted surgery had significantly lower fibrinogen levels than those patients undergone thoracotomy. Pulmonary function decreased during the course of surgery (p=0,001) as well as 6-minute walked distance (p<0,001) and Karnofsky score (p=0,02). Conclusion: Lung cancer patients undergone lung resection had worsened CRP levels, forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), respiratory muscle force and funtional capacity in the first postoperative month. Nonetheless, patients showed improvements in anxiety and depression levels.